Hyperbranched poly (ester) s for delivery of small molecule therapeutics. (21st June 2018) - Zhang, Tracy; Howell, Bob A.; Zhang, Daniel; Zhu, Brandon; Smith, Patrick B.
Abstract : The development of molecular platforms for sustained release of actives is important for both veterinary and personal care applications. A time release platform composed of hyperbranched poly (ester) s (HBPEs) derived from glycerol, a trifunctional bio‐alcohol, and adipic acid, a difunctional bio‐acid, can be readily generated and conjugated with active agents for sustained delivery. The HBPE delivery platform is composed of very inexpensive building blocks that are on the FDA's Generally Regarded As Safe list. Two such active agents, 2‐undecanone and salicylic acid, have been covalently bonded to the HBPE and evaluated for sustained release. 2‐Undecanone is an effective, naturally occurring mosquito repellent, but due to its volatility, it must be reapplied every 15 to 30 minutes. The duration of the effectiveness of 2‐undecanone is enhanced by a sustained release formulation. Salicylic acid and derivatives are widely used for treatment of acne and inflammation, but it causes irritation if dosed at too high a level. A time‐release formulation of salicylic acid would reduce irritation as well as lengthen the duration of its effectiveness. Both actives were covalently bonded to the HBPE and shown to release over time by hydrolysis, either chemically or enzymatically. Moreover, their time release profiles were shown to be a function of composition, catalyst and catalyst level, and physical form.